Oral care in prevention of ventilator-associated pneumonia in neonatal and pediatric intensive care unit: protocol proposal - Lilian Tatiane Bassan; Maria Paula Siqueira de Melo Peres; Juliana Bertoldi Franco (Associação Brasileira de Odontologia, 2018)
Objective: to review the literature on ventilator-associated pneumonia in a neonatal and pediatric intensive care unit, the main substances and vehicles used for oral hygiene, and to propose an oral care protocol for the prevention of ventilator-associated pneumonia, prioritizing the oral comfort and providing a better quality of life. Material and Methods: search in databases from 2000 to 2018, with focus on oral care in neonatal and pediatric intensive care units, using the following descriptors: Ventilator-associated pneumonia; Aspiration pneumonia; Neonatal intensive care unit; Pediatric intensive care unit; Oral hygiene. Results: we selected 26 articles with neonatal and pediatric approach for preparation of the protocol proposal, which must be planned according to the availability of material and human resources, hospital profile, and must be based on scientific evidence. Conclusion: oral care protocols contribute for reducing the risk of infections in intensive care units, reducing the length of stay and hospital costs. Each hospital must develop its own protocol based on available scientific literature and on clinical experience of professionals involved.